Cocoa Farming and Illegal Mining: Farmers’ Perception on the Livelihood Impacts in the Obuasi, Juabeso, and Amansie West Districts of Ghana. - OWUSU, PRINCE; Amoako, Isaac Osei; Asare, Benjamin Wiafe; Dogbe, Prince Yakohene (Indonesian Coffee and Cocoa Research Institute, 2025)
Cocoa and gold are vital contributors to Ghana’s GDP, with many cocoagrowing communities also serving as hotspots for illegal small-scale mining. This study investigated cocoa farmers’ perceptions of the impact of illegal mining on their livelihoods in three districts where both activities coexist. Data was collectedfrom 180 purposively selected cocoa farmers using questionnaires. The findings revealed that illegal mining poses significant challenges, including water pollution, land degradation, cocoa tree mortality, and reduced yields, leading to income losses for farmers. Uncovered mining pits also contribute to health risks suchas mosquito-borne diseases. Key drivers of illegal mining include unemployment, poverty, and quick financial gains from illegal mining activities. The study recommends increased environmental education by the Ministry of Food and Agriculture in collaboration with the Ministry of Lands and Natural Resources to raise awareness among cocoa farmers and mining communities about the adverse effects of illegal small-scale mining on cocoa production and the environment.